The angiogenic gene profile of pulmonary endarterectomy specimens: Initial study - ERMERAK, NEZİH ONUR; YILMAZ, BETÜL; BATIREL, SAİME; OLGUN YILDIZELİ, ŞEHNAZ; KOCAKAYA, DERYA; MUTLU, BÜLENT; YILDIZELİ, BEDRETTİN (My University, 2023)
© 2023 The Author(s)Objectives: The underlying mechanisms for the development of chronic thromboembolic pulmonary hypertension and prognostic biomarkers are not clear yet. Thus, our aim is to assess and identify new biomarkers for the expression of 84 key genes linked to angiogenesis. Methods: Patients who had levels more than 1000 dynes·sec·cm−5 were included in the test group, and the other patients were included in the control group. Twelve specimens were taken from the patients. RT2 Profiler PCR Array (Qiagen) was used to quantify the expression of the 84 key genes. Results: Eight patients (6 male, 2 female, median age 54.4 ± 13.1 years) who underwent pulmonary endarterectomy were included. Pulmonary vascular resistance improved significantly from 811 ± 390 dyn/s/cm−5 to 413.3 ± 144.9 dyn/s/cm−5 (P .005) after surgery. Median length of hospital stay was 11.62 ± 2.97 days. The test group had a distinct pattern of impaired angiogenic and antiangiogenic genes. The expression levels of TGFA, TGFB1, THBS2, THBS1, TGFBR1, SERPINE1, SERPINF1, TGFB2, TIMP2, VEGFC, IFNA1, TNF, CXCL10, NOS3, IGF1, and MMP14 were downregulated in the specimens from the patients who had higher pulmonary vascular resistance values, whereas some genes, including PDGFA, showed upregulation that was statistically nonsignificant in the same group. Conclusions: These results can lead to the development of new markers that could predict adverse outcomes of patients with CTEPH. Identification of new markers that are related to worse outcomes would enable screening patients for early diagnosis and treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Cardiovascular; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; SOLUNUM SİSTEMİ; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; RESPIRATORY SYSTEM; CARDIAC & CARDIOVASCULAR SYSTEMS; Cerrahi; Akciğer ve Solunum Tıbbı; Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Pulmonary and Respiratory Medicine; Cardiology and Cardiovascular Medicine; angiogenesis; chronic thromboembolic pulmonary hypertension; gene expression